MOLTRA-II. New Three Dimensional Descriptors of the Hydrogen Bond - Trepalin, S.V.; Yarkov, A.V.; Raevsky, O.A. (Biomedical Chemistry: Research and Methods, 2018)
The program MOLTRA-II, created on the basis of the CHEmical Databases management system CHED, is supplemented by the possibility of calculating new descriptors based on the three-dimensional structure and hydrogen bond parameters. The program calculates PSA descriptors (Polar Surface Area), OSA (Optimal Structure Area) and energy of the hydrogen bond.